Performance evaluation of helix and spiral receiver geometries for a parabolic solar collector using cfd analysis - Yonanda, Ahmad; Hakim, Naufal; Amrizal, Amrizal; Irsyad, Muhammad; Harmen, Harmen; Riszal, Akhmad; Sinaga, Jorfri Boyke; Haviz, Muhammad (Politeknik Negeri Lhokseumawe, 2025)
This comparative study evaluates the thermal performance of helix and spiral-shaped receivers in a Parabolic Dish Collector (PDC) system, a renewable energy technology that converts solar radiation into heat by concentrating sunlight onto a receiver. The geometry of the receiver significantly influences heat absorption and system efficiency. Using Computational Fluid Dynamics (CFD) simulations, this research compares temperature distribution, fluid flow velocity, and thermal energy transfer between the two receiver designs. Results indicate that the helix receiver provides more uniform heat distribution and achieves 2.6% higher thermal efficiency than the spiral receiver. However, the spiral receiver exhibits higher central flux and benefits from a simpler design and lower production costs. These findings offer insights into selecting optimal receiver geometries for improved solar energy utilization, supporting the advancement of efficient parabolic solar collector technology in renewable energy applications.